2011
DOI: 10.4322/natcon.2011.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Outdoor and Laboratorial Environment Science Activities on Middle School Students Understanding on Conservation

Abstract: This work tested the learning in environmental science education activities involving middle school and undergraduate students. It was verified whether participation just once improved previous knowledge; if biodiversity understanding on the trail is more effective using manual guidance than using instructors' supervision, and if three consecutive activities increase understanding. Activities were conducted with three schools on the Brazilian savannah and consisted of oriented walk on the interpretive trail, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
6
0
2
Order By: Relevance
“…This methodology of teaching in non-formal environments, using the scientific method has been tested with elementary students. It was noted that an interpretative trail associated with laboratory activities, using the scientific method, can help children to approach scientific concepts and the conservation of biodiversity (ANGELINI et al, 2011). These authors also reinforce the results found by Curado and Angelini (2006), for which consecutive activities in Science and Environmental Education, carried out with students from elementary and high schools are more effective than activities performed only once.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…This methodology of teaching in non-formal environments, using the scientific method has been tested with elementary students. It was noted that an interpretative trail associated with laboratory activities, using the scientific method, can help children to approach scientific concepts and the conservation of biodiversity (ANGELINI et al, 2011). These authors also reinforce the results found by Curado and Angelini (2006), for which consecutive activities in Science and Environmental Education, carried out with students from elementary and high schools are more effective than activities performed only once.…”
Section: Resultssupporting
confidence: 66%
“…Although vertebrates and plants are most often used in these activities, aquatic invertebrates have been noted for improving the readings on the environment (ANGELINI et al, 2011). Streams and rivers support communities that tell us the history of the site over a period of time greater than in terrestrial environments, where they are more prone to the climate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So the interpretive nature trails constitute an important component of the support to both the sustainable development of tourism (Topole, 2009) and the inhabitants' environmental awareness (Clark, 1997;Prah & Kolnik, 2007). Although this research showed that the information given at the interpretive trails are adapted to the requirements of the contract owner (Braithwaite & Leiper, 2010) and the consequent behaviour of the visitors does not show any signifi cant changes towards the compliance with the environmental friendliness in the longer-term horizon (Hughes, 2013), their importance regarding environmental awareness is indisputable (Angelini, Simião Ferreira, Santiago do Carmo Araújo, & Rosa Carvalho, 2011).…”
mentioning
confidence: 74%
“…Interpretive nature trails (INT) serve as a major source of sustainable tourism development support (Topole, 2009) and as a means to create an environmentally conscious population (Clark, 1997;Ferreira, 1998). Previous studies have shown that environmental education can encourage pro-environmental behaviour (Jacobs and Harms, 2014), and trails' importance for environmental knowledge is indisputable (Angelini et al, 2011), although some information communicated on trails can be non-objective (Braithwaite and Leiper, 2010), and visitors' future behaviour does not necessarily display more environmental friendliness in the long term (Hughes, 2013). A detailed overview of these papers can be found in Munro, Morrison-Saunders and Hughes (2008).…”
Section: Environmental Education In Tourismmentioning
confidence: 99%